Is river rehabilitation economically viable in water-scarce basins?. Issue 61 (July 2016) - Garcia, X.; Corominas, Ll.; Pargament, D.; Acuña, V.
Highlights: We conducted a cost-benefit analysis of the rehabilitation of a semiarid urban river, considering marketed and non-marketed benefits. Considered benefits were cultural ecosystem services and gene-pool protection, whereas considered costs were implementation costs and foregone benefits to farmers. The rehabilitation of the Yarqon River provided positive net present values despite that the massive water reallocation involved high opportunity costs for farmers. The performed sensitivity analysis determined that the probability of obtaining a positive net present value was 90.8%. We conclude that river rehabilitation becomes a feasible policy decision even in water scarce regions due to the social amenity demand for urban rivers. Abstract: Decisions on river rehabilitation actions are often based on cost-benefit analyses taking into account the costs and benefits of the considered management actions, but ecosystem services are often not included as benefits, despite recent evidences on the effects of river rehabilitations on ecosystem services. A cost-benefit analysis integrating market and non-market costs and benefits was undertaken in this study to assess the economic feasibility of a river rehabilitation project in a water scarce region, the Yarqon River Rehabilitation project (Israel). In this case, the costs included both the capital costs of implementing rehabilitation measures (including maintenance costs) and the opportunity costs of water allocation (foregone benefits to farmers from water provisioning for agriculture). The benefits of rehabilitation included the net marginal benefits of the cultural ecosystem services at local scale (estimated with a hedonic pricing method), and at regional scale (estimated with a value function transfer), in addition to the habitat service gene-pool protection (estimated with a replacement cost method). Bearing in mind the uncertainties surrounding water resource management decisions, especially in water scarce areas, a sensitivity and risk analysis was conducted using an analysis that included both Monte Carlo simulations and the standardized regression coefficients method. The rehabilitation of the Yarqon River provided positive net present values (approximately $139 million in 30-year period). This was thanks to the provision of cultural ecosystem services and despite the high rehabilitation costs, and that the massive water reallocation involved high foregone benefits to farmers. Therefore, these results highlight that river rehabilitation in water scarce regions can be economically viable due to the social amenity demand for urban rivers.